BIM Training: The Impact on BIM Adoption Among Quantity Surveyors in Government Agencies. Issue 2 (February 2019) - Einur Azrin Baharuddin, Har; Faizal Othman, Airul; Adnan, Hamimah; Norizan Wan Ismail, Wan
Abstract: Building Information Modelling (BIM) is extensively known as one of the innovations of Information Technology (IT), globally used as a platform to promote collaborative and integrated working environments in the construction project management. This technology has been vastly modernised and upgraded to become a sophisticated technology for generating and managing project information. Nowadays, BIM is utilised to replace the traditional paper-based drawings as main sources of design information, and as a tool for collaborative working. The aim of this paper is to investigate the impact of BIM training on BIM adoption among quantity surveyors in the government agencies. Training is one of the potential factors that could expedite the adoption of BIM. BIM training is significant due to its role to expand BIM knowledge and to increase BIM usage via hands-on training environment. The results are limited to quantity surveyors who have attended BIM trainings only. From the findings, quantity surveyors within the government agencies do not intend to immediately use BIM despite after attending and participating in BIM trainings due to the lack of understanding of the true BIM values and benefits, even after the participants attended the introductory training, technical training or a combination of both trainings.